Effect of Prey Type on Relationship betweenReproductive Performance and Female’s Age in Macrocyclopsalbidus (Jurine 1820) - Fatimah Ali Ghanim Al-Obadi (Journal of Madenat Alelem University College, 2017)
The present study was conducted to investigate effect of prey type on the relationship between age of females of Macrocyclopsalbidus and reproductive performance, which included each of mean number of nauplii, age at first brood, and age at first clutch. Results revealed that the correlation coefficient between the age at first brood and clutch and age of females fed on Artemia was significant P <0.05, being 0.65 and 0.81 respectively, while the correlations were not significant P>0.05 in females fed on mosquito larvae (Culexquinquefasciatus) and Parameciumnauplii. It was also found that the correlation coefficients between mean number of the nauplii and longevity in M. albidus were significant P<0.05 whereas, the correlations were not significant P>0.05 in the females fed on mosquito larvae. In view of our results, the mosquito larvae could be considered the best prey for the females of the M. albidus compared with the two type of preys (Artemia and Paramecium)as the correlation was negative and significant P<0.01 between the mean number of nauplii and the age of the M. albidus female, which means that the increasing of the number of nauplii is associated with decreasing in female age, while the correlation was negative and not significant P>0.05 between number of nauplii and the age of females fed on mosquito larvae which indicate that the persistency of females represented by the mean number of nauplii/clutch is higher than the two mentioned preys types and that will increase its opportunity to success during the application of the biological control programs of mosquito.